Pengolahan cokelat praline isi tempe dari kacang tunggak, kacang koro benguk dan kacang merah - Wahyu Mushollaeni; Lorine Tantalu; Deni Landu Praing (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Praline chocolate is a type of processed chocolate candy that has various kinds of fillings, including various types of nuts and dried fruit. The development of various types of healthy food which encourages people to combine food products, makes one of the reasons for using tempeh from various types of nuts as a stuffing ingredient in praline chocolate. The aim of the study was to obtain the best combination of cowpea, bean curd, and red bean with the concentration of tempeh fungus (2%, 4%, 6%) to produce peanut tempeh as a raw material for filling in praline chocolate which has the best nutritional quality. The results showed that chocolate praline filled with tempeh with the best nutritional quality was obtained from 6% fermented with tempeh mushrooms.